O Programa PDE paranaense e sua influência sobre as práticas de professores de química - Sá, Marilde Beatriz Zorzi (2014)
This study aimed to investigate the practices of teachers of Chemistry who have worked in the public schools of the city of Maringa after having participated in the Educational Development Program (EDP), a program with features geared towards continuing education of teachers and pedagogical issues. The corpus of data was formed of interviews with those teachers, follow-up reports drawn up by pre-service teachers of Chemistry course who performed the supervised teaching practice in the classes of the mentioned teachers and by the impressions of the researcher due to her experience with the researched. We gathered information about the professional performance of the teachers throughout their careers in basic education and we investigated their perception about possible changes in their practices after participating in the EDP and how they compare their practices in the classroom before and after being involved in that program. This qualitative investigative process made use of the Discursive Textual analysis as theoretical framework. From the interviews and reports emerged categories that make explicit the perceptions of the researched and pre-service teachers concerning the teaching practices. The results show that although the teachers have strong conviction that their practices have improved after the EDP course, the pre-services ' reports and the experience of the researcher indicate that most respondents continues to adopt outdated models of teaching, centered in transmissive practice, heavily dependent on textbook and with little or no attention to dialogical methods or consideration to students ' prior knowledge.